2020
DOI: 10.3390/cells9071710
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 Expression Is Associated with M2 Macrophage Subset in Calcific Aortic Valve Stenosis

Abstract: Calcific aortic valve stenosis (CAVS) is a common age-related disease characterized by active calcification of the leaflets of the aortic valve. How innate immune cells are involved in disease pathogenesis is not clear. In this study we investigate the role of the pattern recognition receptor Toll-like receptor 7 (TLR7) in CAVS, especially in relation to macrophage subtype. Human aortic valves were used for mRNA expression analysis, immunofluorescence staining, or ex vivo tissue assays. Response to TLR7 agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…In support of RvE1 signaling affecting the valvular macrophage subtype, the mRNA levels of its receptor ChemR23 are significantly correlated with the expression of markers of M2-type macrophages in human stenotic valves ( Artiach et al, 2020a ). Similar associations have been reported also for Toll-like receptor (TLR) 7 in stenotic aortic valves and stimulation of macrophages with a TLR7 agonist induced release of the anti-inflammatory cytokine IL-10 ( Karadimou et al, 2020 ), hence reinforcing the role of M2 macrophages in the resolution of valvular inflammation. Moreover, exogenous administration of RvE1 to cultured VIC reduced in vitro calcification, suggesting that omega-3 PUFA-derived SPMs in addition to altering the valvular immune response also directly act on the structural cells of the valve to counteract calcification.…”
Section: Molecular Mechanisms Of Omega-3-derived Rve1 In Avssupporting
confidence: 74%
See 1 more Smart Citation
“…In support of RvE1 signaling affecting the valvular macrophage subtype, the mRNA levels of its receptor ChemR23 are significantly correlated with the expression of markers of M2-type macrophages in human stenotic valves ( Artiach et al, 2020a ). Similar associations have been reported also for Toll-like receptor (TLR) 7 in stenotic aortic valves and stimulation of macrophages with a TLR7 agonist induced release of the anti-inflammatory cytokine IL-10 ( Karadimou et al, 2020 ), hence reinforcing the role of M2 macrophages in the resolution of valvular inflammation. Moreover, exogenous administration of RvE1 to cultured VIC reduced in vitro calcification, suggesting that omega-3 PUFA-derived SPMs in addition to altering the valvular immune response also directly act on the structural cells of the valve to counteract calcification.…”
Section: Molecular Mechanisms Of Omega-3-derived Rve1 In Avssupporting
confidence: 74%
“…Stimulating SPMs and their receptors have beneficial effects in several animal models of intimal hyperplasia ( Artiach et al, 2018 ; Liu et al, 2018 ), atherosclerosis ( Petri et al, 2017 ), and vascular calcification ( Carracedo et al, 2018 ). Recently, studies on SPM pathways ( Artiach et al, 2020a ) and M2 macrophages ( Karadimou et al, 2020 ) pointed toward a failure in the resolution of inflammation as part of the pathophysiological processes underlying the chronic inflammation in AVS.…”
Section: The Resolution Of Inflammationmentioning
confidence: 99%
“…8 A and 8I-K), which indicated that M1 macrophages were activated and the infiltration of M2 macrophages decreased in the tumor sites after the Dox/hydrogel treatment. We also found that the rate of CD206+ cells in the co-delivering treated group showed no significant difference compared with that of the control group, which might due to the stimulation of R837 on M2 macrophages [ 54 ]. In a word, the analysis of infiltrated immune cells revealed that multiple types of immune promoted cells have been activated and infiltrated in the tumor sites after the co-delivering treatment, while the infiltration of immune suppressive M2 macrophages decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Toll-like receptors are expressed by VICs. They promote osteogenic phenotype of VICs [51,52]. NFκB is activated by TNFα from T-lymphocytes and macrophages [53].…”
Section: Inflammationmentioning
confidence: 99%